2011
DOI: 10.4049/jimmunol.1004095
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Response to Influenza Vaccine Associated with Persistent Memory B Cell Depletion in Non-Hodgkin’s Lymphoma Patients Treated with Rituximab-Containing Regimens

Abstract: Influenza vaccination is generally recommended for non-Hodgkin’s lymphoma (NHL) patients, but no data are available about the activity of this vaccine after treatment with rituximab-containing regimens. We evaluated the humoral response to the trivalent seasonal influenza vaccine in a group of NHL patients in complete remission for ≥6 mo (median, 29 mo) after treatment with rituximab-containing regimens (n = 31) compared with age-matched healthy subjects (n = 34). B cell populations and incidence of influenza-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 42 publications
7
64
0
1
Order By: Relevance
“…16 Some studies with limited patient numbers have suggested that rituximab has a negative impact on response to influenza vaccine, both during treatment 12,13 and more than 6 months after treatment. 14 Takata et 12 and van der Kolk et al reported a reduced immune response after rituximab therapy in 11 patients. 13 Bedognetti et al found significantly lower responses to the 2008-2009 seasonal vaccine in 31 non-Hodgkin lymphoma patients treated with rituximab-containing regimens.…”
Section: Org Frommentioning
confidence: 99%
See 2 more Smart Citations
“…16 Some studies with limited patient numbers have suggested that rituximab has a negative impact on response to influenza vaccine, both during treatment 12,13 and more than 6 months after treatment. 14 Takata et 12 and van der Kolk et al reported a reduced immune response after rituximab therapy in 11 patients. 13 Bedognetti et al found significantly lower responses to the 2008-2009 seasonal vaccine in 31 non-Hodgkin lymphoma patients treated with rituximab-containing regimens.…”
Section: Org Frommentioning
confidence: 99%
“…14 Unlike our study, these 31 patients had completed treatment 6 months or more before vaccination. 14 The present study represents the first large controlled study aimed to investigate humoral responses to influenza vaccination in lymphoma patients treated with rituximab as a single agent or in combination with chemotherapy. No vaccine-induced protective immunity was observed in any cases against the influenza A (H1N1) 2009 ("swine flu") virus.…”
Section: Org Frommentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there are no reports describing vaccine efficacy in rituximab-treated AIBD patients. Previous studies have reported severely impaired immune responses to influenza vaccination in other types of rituximab-treated patients, primarily RA or lymphoma patients (30)(31)(32)(33)(34). A major caveat to these earlier studies is that patients were treated with concomitant immunosuppressive drugs or chemotherapy, making it difficult to determine the effect of the individual drugs on vaccine responses.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no direct evidence that B-cell depletion and/ or loss of function would be beneficial in asthma, and loss of regulatory B cells exacerbates allergic airway inflammation in mice (Amu et al, 2010). Furthermore, compromising B-cell function may even be deleterious in patients with asthma who rely on vaccine protection from respiratory viruses (e.g., influenza) to prevent exacerbation (Wells et al, 2015), and there is evidence that B-cell depletion impairs response to the influenza vaccine (Bedognetti et al, 2011). However, fostamatinib demonstrated no effect on IgG or IgM responses after keyhole limpet hemocyanin challenge, nor did it affect bacterial or viral clearance in listeria, streptococcal, or influenza host-resistance mouse models (Zhu et al, 2007), suggesting that B-cell responses may not be impaired, even at higher exposures that cover the CD69 activation assay.…”
Section: Syk Inhibitor With Differential Cellular Pharmacologymentioning
confidence: 99%